Experimental study of stability, quench propagation and detection methods on 15 kA sub-scale HTS fusion conductors in SULTAN. (1st February 2023) - Bykovskiy, N; Bajas, H; Dicuonzo, O; Bruzzone, P; Sedlak, K
Abstract: High-temperature superconductors (HTSs) enable exclusive operating conditions for fusion magnets, boosting their performance up to 20 T generated magnetic fields in the temperature range from 4 K to 20 K. One of the main technological issues of HTS conductors is focused on their protection in the case of thermal runaway (quench). In spite of the extremely high thermal stability of HTS materials, quenching is still possible due to local defects along the conductor length or insufficient cooling. In such cases, the high stability results in the slow propagation of a resistive zone. Thereby, a risky hot-spot temperature (>200 K) can be reached if applying conventional quench detection methods at a voltage threshold of 0.1–0.5 V, typical for fusion magnets. Aiming at an experimental study of the phenomenon, a series of sub-scale 15 kA 3.6 m long conductors based on stacks of tapes soldered in copper profiles are manufactured at the Swiss Plasma Center, including twisted rare earth barium copper oxide (ReBCO) and bismuth strontium calcium copper oxide (BISCCO) triplets, non-twisted and solder-filled ReBCO triplets, as well as indirectly cooled non-twisted ReBCO single strands. Applying either an increasing helium inlet temperature, overcurrent operation or energy deposited by embedded cartridge heaters, critical values of the electric field and temperature are evaluated for a given operating current (up to 15 kA) and background magnetic field (up to 10.9 T). Once quenching is actually triggered, the quench propagation is studied using distributed voltage taps and temperature sensors able to monitor the external temperature of the jacket and the internal temperature of the conductor (helium or copper). Thanks to the recent upgrade of the Supraleiter Test Anlage (SULTAN) test facility, quench propagation in the conductors is measured up to a total voltage of 2 V and a peak temperature of 320 K. Furthermore, advanced quench detection methods based on superconducting insulated wires and fiber optics are also instrumented and studied. A summary of the test samples, their instrumentation and corresponding test results are presented in this work.